Analysis of critical thinking skills, cognitive learning outcomes, and student activities in learning the human excretory system using an interactive flipbook - Aswanti, Novita Hawsari; Isnaeni, Wiwi (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
This study aims to: (1) analyze the achievement of critical thinking skills, (2) analyze the achievement of cognitive learning outcomes, (3) determine the learning activities carried out, and (4) determine student responses to the use of interactive flipbook media. This study is Quasi Experiment research with a posttest-only control design employing a purposive sampling technique. The data in this study are (1) data on the achievement of critical thinking ability indicators, (2) data on achievement of cognitive levels (C4, C5, and C6), (3) data on student learning activities carried out, and (4) data on student responses to use of interactive flipbook media. The instruments used are (1) critical thinking tests in the form of description questions, (2) cognitive learning outcomes tests in the form of multiple-choice questions, (3) student activity observation sheets, and (4) student response questionnaires. The results obtained in learning the human excretory system using interactive flipbooks are: (1) the level of achievement of critical thinking skills on each indicator can be achieved well, (2)the level achievement of cognitive learning outcomes (C4, C5, and C6) in each category can be achieved well, (3) learning activities that appear and implement in the learning process include visual activities, oral activities, and listening activities, and (4) the use of interactive flipbook media gets a positive response from students. Most respondents agree to use interactive flipbook media to learn the human excretory system. Students also assess that interactive flipbook media are interesting, flexible, practical, meaningful, and not dull.